The Determinants of Microinsurance Demand in South Africa - Morekwa, Edger (School of Economics, 2024)
Low-income households face significant risk that influence their financial decisions and perpetuate poverty. This population group is adversely affected by illnesses, natural disasters, unemployment, and accidents than other groups because, among other things, they lack proper insurance. Microinsurance was introduced as a revolutionary tool with the potential to prevent poverty traps and offer reliable and affordable risk mitigation options to the poor. By providing replacement revenues in the event of insured losses and boosting positive outcomes, microinsurance can significantly reduce the welfare costs related to uninsured risks. Over the years, the take up rate of microinsurance have been low and declining. The study seeks to shed light on the determinants of microinsurance demand in South Africa.